Clinical remission trajectories and histopathological associations in patients with IgA nephropathy treated with targeted-release budesonide: a real-world cohort study - Dafeng He; Jun Xu; Bo Gao; Mingzhu Jiang; Wenjin Liu; Chuanyan Zhao; Xinrui Li; Chunlei Lu; Mengyue Zhu; Hongbin Mou; Guangyu Bi (Frontiers in Immunology, 2026)
Background Targeted-release (TR) budesonide provides upstream mucosal immunomodulation in IgA nephropathy (IgAN) by targeting the gut-associated lymphoid tissue. However, the extent to which distinct downstream immune-inflammatory phenotypes and established structural chronicity shape real-world remission trajectories remains insufficiently characterized. Methods We retrospectively analyzed 57 adults with biopsy-proven primary IgAN treated with TR-budesonide. Prespecified milestones were Very Early Response (VER) at 3 months, Early Response (ER) at 6 months, and composite clinical remission (complete or partial remission, CR/PR) over 12 months. We constructed a time-dependent prognostic nomogram using multivariable Cox modeling integrating the full Oxford MEST-C spectrum and concurrent therapies, strictly applying optimism-corrected bootstrapping (1,000 iterations) to ensure robust internal validation. Results Relative proteinuria reductions were broadly comparable across MEST-C strata, even among patients with substantial baseline chronicity (S1, 91.2%; T1/T2, 63.2%). Concomitant sodium–glucose cotransporter 2 inhibitor (SGLT2i) therapy independently predicted VER (OR 9.40, 95% CI 1.36–64.92; P = 0.023), consistent with an early complementary kinetic profile. Over 12 months, endocapillary hypercellularity (E1) was the only independent histopathological factor associated with composite remission (OR 2.20; P = 0.022) and was associated with a shorter time to remission (log-rank P = 0.031). The resulting optimized 3-variable nomogram demonstrated good discrimination (time-dependent AUC 0.79 at 6 months and 0.83 at 12 months) with favorable internal calibration. Conclusions In routine practice, the antiproteinuric effect of TR-budesonide appears largely preserved even in patients with advanced tubulointerstitial fibrosis. Early response is strongly associated with concomitant SGLT2i therapy, while the E1 lesions was associated with a faster trajectory toward composite clinical remission within this treated cohort, identifying a potentially reversible inflammatory phenotype that warrants further validation. These findings highlight the translational value of integrating histopathological phenotyping to characterize real-world remission trajectories.